Thinking and its development approaches: The 2nd third of al-Quran al-Karim as a case study / Galal Abdullah Ahmed Saif - Galal Abdullah, Ahmed Saif (2018)
The Holy Quran represents a book of education and preparation of the human as a Khilāfah (man who constructs earth and follows the religion of Allah on the earth). This study comes to clarify the Quranic vision of education، especially in developing the faculty of thinking and elevating it to an advanced level. This makes it able to carry the responsibilities of succession (Khilāfah). This study aimed to explain the cognitive aspect of thinking in Quran، highlights the concern of Quran in developing thinking، and demonstrates the methods used in Quran to enhance thinking abilities. The study is also intended to reveal the extent to which the second third of the Quranic chapters consisting of those methods and how they are distributed in this second third of the Holly Quran. Inductive method and content analysis are used to achieve the aims of this study. The Study results show that thinking is mentioned in Quran in a nature that aims for continuity and renewal in Khilāfah on earth. It is also shown that thinking is mentioned in Quran as an obligation of worship and necessity to lead life. The study finds that thinking in Quran aims for noble goals that make it a tool to build and develop life. It is also shown that Quran includes a number of principles that encourage thinking and provides solutions to its obstacles. The study also reveals some approaches used in Quran that establish an educational strategy to develop thinking. The Impact of methods used to develop thinking as mentioned in Quran is also shown in this study، such as giving directions، storytelling، dialogue، asking questions، sayings، showing miracles and signs of the universe، in addition to motivation. Such methods are found to be widely used in the second third of Quran، in particular، Surah al-Naḥl followed by Surah al-Anbiyā، al-Shucarā، and Surah al-Nūr، respectively. Among the methods، showing signs of universe were asking questions، giving directions، storytelling، and motivation، respectively. Finally، it was found that، in the second third of Quran، such methods were used in the Mecci verses more than the Madani verses.